Competencies Needed for Vocational Education Graduates in Logistic Industry: A Systematic Review - Dwiyanti, Vina; Wulansari, Dwi Novi; Okitasari, Hanissa (Online Journal for TVET Practitioners, 2021)
Logistics is one of the industries that constantly follows developments, changes, and shifts. At this time, the competence of vocational education graduates, especially in logistics, has not adjusted the demands and needs of the industry. Vocational education certainly must prioritize the competence of suitable graduates, have high qualifications is appropriate for the logistics industry. This research aims to find the competence of vocational education graduates in the logistics field that are by industry demands and needed. This study used the Systematic Literature Review (SLR) method using data sources from previous studies that have been published in indexed international and national journals for the year published between 2010-2020. The findings of this study indicate the need for vocational education graduates to be equipped with hands-on skills, soft skills that are relevant to the industry with massive changes, shifts, and challenges, and competence to predict future challenges. Vocational education graduates should have a good competency to fulfill logistics industry needed.